2001
DOI: 10.1002/jcp.10040
|View full text |Cite
|
Sign up to set email alerts
|

Goniodomin A, an antifungal polyether macrolide, exhibits antiangiogenic activities via inhibition of actin reorganization in endothelial cells

Abstract: Goniodomin A (GDA) is an antifungal polyether macrolide isolated from the dinoflagellate Goniodoma pseudogoniaulax. Previous studies revealed that GDA profoundly affected cytoskeletal reorganization. We examined the effect of GDA on the angiogenic properties of vascular endothelial cells. GDA itself did not affect proliferation of, migration of, and tube formation in type I collagen gels by, bovine aortic endothelial cells (BAECs). Proliferation of BAECs stimulated by bFGF was not affected by GDA at concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…In this study, the treatment of cholangiocarcinoma cells with bFGF increased actin polymerization formation and cell migration. These findings are consistent with a previous study demonstrating that bFGF induced stress fiber formation in cancer cells (18). Taken together, these observations suggest that bFGF induces cholangiocarcinoma cell migration via the regulation of actin organization.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the treatment of cholangiocarcinoma cells with bFGF increased actin polymerization formation and cell migration. These findings are consistent with a previous study demonstrating that bFGF induced stress fiber formation in cancer cells (18). Taken together, these observations suggest that bFGF induces cholangiocarcinoma cell migration via the regulation of actin organization.…”
Section: Discussionsupporting
confidence: 93%
“…Pharmacological research carried out on this substance indicated that goniodomin A has extreme effects on the reorganization of the cytoskeleton. Abe et al (2002) found that this compound inhibited angiogenic properties of endothelial cells partly by inhibition of actin reorganization. The findings from Furukawa et al (1993) suggested that goniodomin A causes a conformational change resulting in an enhancement of actomyosin ATPase activity at concentration < 10 À6 M, but conformational changes at concentrations > 10 À6 M may lead to a loss of ATPase activity in rabbit skeletal muscle.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, microtubule-stabilizing agents, including paclitaxel and taxane derivatives [127,128], affect FGF2-triggered angiogenesis in vitro and in vivo. Also, by preventing the formation of stress fibers, the antifungal polyether macrolide goniodomin-A inhibits FGF2-induced migration and morphogenesis in ECs, leaving unaffected their proliferation [129]. These findings are of importance [240], angiogenesis [241], EC monolayer wound repair a proliferation [240] angiogensis [241] morphogenesis, angiogenesis [242] proliferation, angiogenesis [243] PD 098059 U0126 apigenin ERK1/2…”
Section: Inhibiting Fgf-activated Ec Responses/effectors Of Angiogenesismentioning
confidence: 97%